Demokrasi Dialogis dalam Kepemimpinan Joko Widodo dan Basuki Tjahaja Purnama (Gubernur dan Wakil Gubernur Dki Jakarta) - Ruman, Yustinus Suhardi (Bina Nusantara University, 2013)
The substantive of democracy is not merely liberative relaying on the function of the democracy institutions. In addition, the substantive of democracy does not occur because of the openness of public sphere for public debates. Through observing the phenomena of democracy practiced by Joko Widodo and Basuki Tjahaja Purnama as Governor and Vice Governor of DKI Jakarta, this article wants to explain that the practices of democracy in this era have significant evolution. The practices of democracy are not limited to liberative and deliberative practices. The practices of democracy have arrived on dialogue practices. To explain the dialogue democracy as practiced by Joko Widodo and Basuki Tjahja Purnama, this article used the concept dialog democracy.